10 years of Lusi eruption: Lessons learned from multidisciplinary studies (LUSI LAB). (February 2018) - Mazzini, Adriano
Abstract: The spectacular Lusi eruption started in northeast Java, Indonesia, on May 29 th, 2006, continuously erupting mud, water, gas, oil, and clasts ever since. Lusi provides an unprecedented opportunity to study the birth and the evolution of a large-scale and hot mud eruption. Lusi is interpreted as a hybrid between a traditional hydrocarbon-driven piercement structure (mud volcano) and a hydrothermal system fuelled by magmatic heat. Lusi is therefore an exciting natural laboratory for understanding analogue modern and palaeo-piercement systems such as mud volcanoes, sediment-hosted hydrothermal systems, and hydrothermal vent complexes. This special issue collects recent multidisciplinary work completed in the framework of the ERC-funded LUSI LAB project. These studies were conducted at and near Lusi. Contributions span across disciplines such as engineering, geochemistry, geophysics, geology and numerical modelling, including fieldwork, laboratory and theoretical approaches. The acquired results contribute to characterise the dynamics of complex interactions between volcanism and an ongoing erupting clastic system. Lusi still saves many mysteries that will be unravelled by future scientific investigations.